Pengaruh Pemberian Sosis Fermentasi terhadap Pertumbuhan Tikus Percobaan - Ernaningsih, D.; Arief, I. I.; Taufik, E. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2014)
Dietary changes can increase the risk of degenerative diseases. The risk can be reduced by consuming healthy food, food that not only meets the needs of nutrition but also provide health benefits. Food that has both of these functions is called a functional food. Components that can be added into the food in order to have functional value is probiotic bacteria. Lactobacillus plantarum IIA-2C12 that isolated from local beef at Bogor was added in the process of  meat processing into fermented sausage and than tasted by in vivo. The aims of this study was to examine the influence of the probiotic fermented sausage using L. plantarum IIA2C12 as probiotica cultures on growth status of rats. This research was conducted in two stages, first bacterial starter culture refreshment and sausage making; second testing in rats (in vivo). The initial population of L.plantarum IIA-2C12 was 9. 27 log cfu mL  and after processing into fermented sausage bacteria became 8. 67 log cfu/g so that sausage could be categorized as a probiotic food. Feeding fermented sausages and sausages for 10 days had no significant effect (P>0.05) body and organ weights of rats. While the fermented sausage had highest feed convertion ratio than kasin and nonfermented sausage.